EFEKTIFITAS BAWANG MERAH TERHADAP PENURUNAN SUHU TUBUH PADA ANAK FEBRIS USIA 1 â 5 TAHUN - Nugroho, Christianto (Akademi Keperawatan Pamenang, 2012)
Fever are circumstances when individuals experiencing or at risk of increased body temperature continuously for more than 37.80 C (1000F) per oral or 38.90 C (1010F) per rectal due to external factors) lt can be said that normal body temperature when the temperature is 36.50 C - 37,50C. The purpose of this study is to determine the effectiveness of red onion to the decrease of body temperature in children aged 1-5 years with fever. The research design used in this study is